Komparasi Output Termoelektrik Generator ( Kuat Arus Dan Tegangan ) Pada Jalas Aspal Dan Beton Dengan 3 Variasi Bentuk Plat Tembaga - Luthfi Afiif Yazu; Rahmat Iman Mainil; Azridjal Aziz (Sekolah Tinggi Teknik PLN, 2022)
Solar radiation heat energy is energy that propagates throughout the earth's surface and is absorbed stored in various objects on the earth's surface. A thermoelectric generator is an electrical generator device that converts heat (temperature difference) directly into electrical energy, using a phenomenon called the Seebeck effect. In this research, this research was carried out by utilizing the absorption of solar radiation heat on a concrete road with a type of cast concrete class III with K 250 and asphalt type AC-WC as a thermoelectric generator. This research uses 3 thermoelectric generator modules type 1848 which will be arranged in series, the cooling system is filled with water using 2 asphalt and concrete variables, each of which has three variations of L, I and Z-shaped heat conductor plates. The test results show that asphalt has energy larger than concrete. L plate is the best plate on both asphalt and concrete roads. This research allows it to be developed to become a reference source of the latest alternative energy. Keywords: Heat Energy, Thermoelectric generator, Plate variation